2020
DOI: 10.1111/cdep.12384
|View full text |Cite
|
Sign up to set email alerts
|

The Early Ontogeny of Reason Giving

Abstract: The key context within which preschool children learn to justify beliefs with reasons is collaborative problem‐solving and decision‐making with peers, including in the moral domain, in which they engage with another coequal mind in a cooperative spirit. Evidence for this proposal comes from recent studies in which children demonstrated sensitivity to the common ground assumptions they shared with their peer partners in decision‐making, as well as an ability to provide reasons relevant to their shared understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Our findings highlight that having a disagreement or conflicting perspectives in the context of collaborative problem-solving is crucial for prompting children to provide reasons for their claims (Köymen & Tomasello, 2018, 2020) and refer to gossip in our studies. Children and their partners received conflicting information in both conditions, but we manipulated the “relevance” of the gossip across the two conditions.…”
Section: Discussionmentioning
confidence: 72%
“…Our findings highlight that having a disagreement or conflicting perspectives in the context of collaborative problem-solving is crucial for prompting children to provide reasons for their claims (Köymen & Tomasello, 2018, 2020) and refer to gossip in our studies. Children and their partners received conflicting information in both conditions, but we manipulated the “relevance” of the gossip across the two conditions.…”
Section: Discussionmentioning
confidence: 72%
“…Interestingly, we found across both experiments that children intervened more often in conventional than in moral situations. One possible interpretation of these findings is that children's main motivation for intervening was to teach the puppet about the norm because conventional norms can less easily be inferred from observing the consequences of one's action than moral norms against physical harm (Köymen & Tomasello, 2020). Clearly, however, alternative explanations of why children intervened more often in the conventional than in the moral conditions are possible.…”
Section: Discussionmentioning
confidence: 99%
“…Producing meta‐talk requires speakers to reflect on their partners’ reasons, as well as their own reasons, and explain which set of reasons are better, a crucial ability in making rational collaborative decisions (Köymen & Tomasello, 2020; Mercier & Sperber, 2011). In two studies, we have demonstrated that starting at age 3, children spontaneously produce reasons based on eyewitness to justify their better knowledge access compared to their partner.…”
Section: Discussionmentioning
confidence: 99%